2018
DOI: 10.1002/jcla.22389
|View full text |Cite
|
Sign up to set email alerts
|

Increased concentration of serum periostin is associated with poor outcome of patients with aneurysmal subarachnoid hemorrhage

Abstract: Elevated serum periostin concentrations are significantly associated with clinical severity and poor outcome of aSAH patients, which indicate serum periostin can be used as a prognostic biomarker in patients with aSAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Previous studies found that increased periostin levels were associated with clinical severity and poor outcome in patients with traumatic brain injury 17 , aneurysmal subarachnoid haemorrhage 18 , and ICH 16 . In the present study, the increased periostin levels observed in the first 6 days or within 4 weeks after IS were correlated with the NIHSS scores, indicating that the new accumulation of periostin in the circulation might reflect the degree of IS severity.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies found that increased periostin levels were associated with clinical severity and poor outcome in patients with traumatic brain injury 17 , aneurysmal subarachnoid haemorrhage 18 , and ICH 16 . In the present study, the increased periostin levels observed in the first 6 days or within 4 weeks after IS were correlated with the NIHSS scores, indicating that the new accumulation of periostin in the circulation might reflect the degree of IS severity.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, post-SAH increases in POSTN may cause EBI, which in turn may lead to DCI with no vasospasm [13]. In fact, a previous clinical study reported positive correlation between admission WFNS grade, which may reflect the severity of EBI, and pretreatment peripheral blood POSTN levels [14]. In the present study, admission WFNS grade and plasma POSTN levels at days 1-3 were negatively correlated, but this may be because poor-grade patients more frequently underwent CSF drainage, resulting in lower plasma POSTN levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that POSTN was upregulated in cerebral cortex after SAH in mice and was responsible for early brain injury (EBI) in terms of blood-brain barrier (BBB) disruption [13]. There has been only one paper published in a clinical setting, in which admission and pretreatment peripheral blood levels of POSTN were related to clinical severity, DCI, and poor outcomes after aneurysmal SAH [14]. However, it remains unknown how peripheral blood POSTN levels change with time, and if various treatments that are performed for aneurysmal obliteration or prevention of DCI influence peripheral blood POSTN levels.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent discrepancy may be resolved by future studies to clarify how periostin relates with each integrin subtype in cerebrovascular diseases. In a clinical setting, a higher serum periostin level at admission was associated with worse initial neurological status, greater hemorrhage volume, more frequent development of DCI, and worse clinical outcomes in patients with aneurysmal SAH ( 116 ). In addition, plasma periostin levels increased before the development of DCI, irrespective of the presence or absence of CVS ( 108 , 117 ).…”
Section: Contribution Of Other Mcps To Regulating Tnc Expression In Smentioning
confidence: 99%